Spectrum of Clostridium difficile infections: Particular clinical situations. (February 2016) - Bouza, Emilio; Del Vecchio, Marcela González; Reigadas, Elena
Abstract: Incidence, pathogenesis, diagnostic techniques and therapeutic management of CDI have prompted abundant and adequate recent literature. However, report on clinical manifestations of CDI is frequently biased by the type of patients selected, the retrospective nature of many papers, the epidemic or endemic characteristics of the population reported. This article seeks to review some less discussed clinical and epidemiological aspects of CDI trying to include the clinical manifestations of this disease in unselected populations and also including discussion of CDI in specific groups of patients such as patients without colon and rectum, pediatric and critical care patients. Highlights: CDI awareness should be extended to young aged patients and community cases. CDI should be considered in patients with WBC ≥15, 000 cells/mm 3 even without diarrhea. Non-colonic CDI is uncommon, its clinical significance is difficult to assess. CDI acquired in the ICU is not associated with an increased risk of mortality.